Autism spectrum disorder: an early and frequent feature in cerebrotendinous xanthomatosis. Issue 4 (11th September 2017) - Stelten, Bianca M. L.; Bonnot, Olivier; Huidekoper, Hidde H.; van Spronsen, Francjan J.; van Hasselt, Peter M.; Kluijtmans, Leo A. J.; Wevers, Ron A.; Verrips, Aad
Abstract: Background: Cerebrotendinous xanthomatosis (CTX) is an autosomal recessively inherited inborn error of metabolism (IEM) due to mutations in the CYP27A1 gene. The clinical picture ranges from being nearly asymptomatic in early childhood, up to severe disability at adult age. Infantile‐onset diarrhea and juvenile‐onset cataract are the earliest symptoms in childhood. In the current study, we evaluated the presence of autism spectrum disorder (ASD) in a large cohort of CTX patients. Methods: We performed a retrospective patient file study in 77 genetically confirmed Dutch CTX patients to determine the frequency of ASD. In addition, we compared plasma cholestanol levels in CTX patients with and without a diagnosis of ASD and tried to establish a relation between CYP27A1 genotype and ASD. Results: In our CTX cohort, 10 patients (13%; nine pediatric and one adult) with ASD were identified. At the time of diagnosis of ASD, most patients only exhibited symptoms of diarrhea and/or intellectual disability without signs of cataract or neurological symptoms. No correlation was found between the presence of ASD and the level of cholestanol or CYP27A1 genotype. The behavioral problems stabilized or improved after treatment initiation with chenodeoxycholic acid (CDCA) in all pediatric patients. Conclusions: We conclude that ASD is an early and probably underestimated frequent feature in CTX. Metabolic screening for CTX should be performed in patients with ASD when accompanied by diarrhea, intellectual disability, juvenile cataract, and/or neurological involvement. Early recognition allows for earlier initiation of specific treatment and will improve clinical outcome. Our results add CTX to the list of treatable IEMs associated with ASD.